Effect of Tactile Walking Surface Indicators on Travelers with Mobility Disabilities. Issue 7 (July 2020) - Bentzen, Billie Louise (Beezy); Scott, Alan C.; Wall Emerson, Robert; Barlow, Janet M.
Guidance tactile walking surface indicators (TWSIs), typically a surface of raised bars, are used internationally to provide location and directional information at crosswalks to pedestrians who are blind. The bars are installed across the sidewalk, with the bars perpendicular to the travel path on the sidewalk and parallel to the direction of travel on the crosswalk. In the U.S., there has been little or no use of such surfaces at crosswalks because of concerns about the effect of these bars on individuals with mobility disabilities. However, difficulties of blind pedestrians in locating crosswalks and aligning to cross have been documented, and the installation of surfaces with bars parallel to the direction of travel on the sidewalk has been shown to be a possible solution. This research investigated the effects of crossings of TWSIs installed perpendicular versus parallel to the direction of travel on the sidewalk on 38 participants with mobility disabilities who used a variety of mobility aids. Crossing either orientation of bars caused some increase in effort and instability for more than half of participants. Effort was somewhat greater on average for all participants when crossing bars perpendicular to their travel. Stability for wheelchair users was poorer, on average, when the bars were oriented perpendicular to their travel. There was low incidence of any slipping of feet or mobility aids, and low incidence of trapping of wheels or cane/crutch/walker tips. A significant majority of participants expressed their preference for crossing bars oriented parallel to their travel.